Stink and the great Guinea Pig Express - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2008)
Stink Moody, friends Webster and Sophie, and Mrs. Birdwistle visit tourist attractions in Virginia as they try to give away 101 guinea pigs rescued from a laboratory, although Stink is very reluctant to give away his favorite, Astro.
640
Keywords: Guinea pigs -- Fiction; Animal rescue -- Fiction; Automobile travel -- Fiction; Humorous stories; Virginia -- Fiction